2001
DOI: 10.1034/j.1600-0633.2001.100307.x
|View full text |Cite
|
Sign up to set email alerts
|

Estuarine predation on radiotagged wild and domesticated sea trout (Salmo trutta L.) smolts

Abstract: – Avian predation on emigrating wild and domesticated sea trout smolts was investigated in a fjord in the western Baltic Sea. In April 1997, 50 domesticated and 50 wild smolts were intraperitoneally tagged with radio‐transmitters and released in a small coastal stream. Predation was recorded by signal interception in an estuarine breeding colony of cormorants and herons near the outlet of the stream. Of the 78 emigrating smolts, 51 (65%) were recorded as eaten. Predation rates were significantly higher among s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 18 publications
6
73
2
Order By: Relevance
“…Predation is an important mortality factor for fish compromised by parasites, and this is even worse for small fish that are vulnerable to predation in the first place (Dieperink et al, 2001;Krko sek et al, 2011;Peacock et al, 2015). Even though the observed mortality for small fish in the present study is higher than expected from laboratory studies, it is likely to still be an underestimate of the total sea migration mortality.…”
Section: Migratory Behaviourcontrasting
confidence: 55%
See 1 more Smart Citation
“…Predation is an important mortality factor for fish compromised by parasites, and this is even worse for small fish that are vulnerable to predation in the first place (Dieperink et al, 2001;Krko sek et al, 2011;Peacock et al, 2015). Even though the observed mortality for small fish in the present study is higher than expected from laboratory studies, it is likely to still be an underestimate of the total sea migration mortality.…”
Section: Migratory Behaviourcontrasting
confidence: 55%
“…Even though the observed mortality for small fish in the present study is higher than expected from laboratory studies, it is likely to still be an underestimate of the total sea migration mortality. Sea migration mortality may be expected to be highest during the first 14 days after sea entrance (Dieperink et al, 2001;Middlemas et al, 2009), and we tagged sea trout post-smolt that had been to sea for an unknown period. Also, we tagged relatively large trout and tracked the sea trout for a relatively short time (over one summer as opposed to over a lifetime).…”
Section: Migratory Behaviourmentioning
confidence: 99%
“…In addition, the existence of still and relatively deep waters upstream of weirs facilitates foraging by diving birds and negates the refuge afforded by the turbulence of riffles. Two important bird predators in the salmon rivers of the Iberian Peninsula include the great cormorant (Phalacrocorax carbo (L.)) and the heron (Ardea cinera L.), both of which can have a significant effect on salmonid populations (Kennedy & Greer, 1988;Dieperink et al, 2001;Serdio et al, 2003). Data from the R. Asón indicates that the distribution of great cormorants along the river course is closely related to the location of weirs (Fig.…”
Section: Predationmentioning
confidence: 96%
“…The decrease aligned with an increase in the great cormorant populations that are found on the Swedish East coast (Bregnballe et al, 2003). Studies have shown that hatchery reared smolts are more vulnerable to predation by birds than wild smolt (Kennedy and Greer, 1988;Dieperink et al, 2001). Reasons for this that have been discussed are poorer performance, less exercised, more 1994-2006. surface oriented and less experienced with predators.…”
Section: Introductionmentioning
confidence: 92%